Protein-protein interaction networks - Csermely, Peter (Henry Stewart Talks, 2012)
General features of networks, Creative network nodes, Overview of cellular networks, Definition and databases of protein-protein interaction networks, Main methods to identify protein interaction data and their quality, Small worldness, hubs (date and party hubs, rich clubs) and modules of protein-protein interaction networks, Change of modular overlaps as an efficient method of adaptation